A Case of Spontaneous Regression of Pulmonary Small Cell Carcinoma - Ugajin, Motoi (Eur J Case Rep Intern Med, 2019)
An 82-year-old man was examined using chest computed tomography after treatment for pneumonia. Imaging showed a nodular shadow in the left lower lobe with associated enlarged lymph nodes. A polypoid tumour was observed on bronchoscopic examination, and the histological findings showed pulmonary small cell carcinoma with infiltration of CD3-positive and CD8-positive lymphocytes. The patient declined any antitumoural therapy and experienced an exacerbation of heart failure treated with atrial natriuretic peptide. Eighteen months after the diagnosis, the polypoid tumour had disappeared. T lymphocyte-mediated immunity and the antitumoural effects of atrial natriuretic peptide may have influenced the observed spontaneous regression. LEARNING POINTS: Spontaneous regression of pulmonary small cell carcinoma is an exceptional phenomenon. T lymphocyte-mediated immunity and the administration of atrial natriuretic peptide may have affected the observed spontaneous regression of pulmonary small cell carcinoma.